Analisis Korelasi Lama Pemakaian Kb Iud Dengan Kejadian Menorrhagia Pada AkseptorKB IUD - Roifah, Ifa; Sofenti Priasninuri, Rima (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstractThe use of IUDs on some family planning acceptors often has side effects of menorrhagia, Menorrhagia is longer menstrual bleeding and blood volume is spent more. Mcnorrhagia that occurs often leads to drop-outs on IUD familyplanning users. The purpose or this study is to determine the relationship between the length or use or IUD KB with theincidence of mcnorrhagia on IUD family planning acceptors in Sumolawang Vil lagc, Puri District, Mojokcrto Regency.The research design used is corrclational analytics. The population in chis study were all IUD family planning acceptors in Sumolawang vi I Iage, Puri sub-district, Mojokerto regency. The sample size was 48 respondents. the sampling technique using Simple Random Sampling. tested using Spearman Rank Test. The results showed that more than half of respondents had used TUD KTI with the duration of use> 1 year as many as 26 respondents (54.2%). For the occurrence of menorrhagia, the results of the study found that most respondents did not experience menorrhagia as much as 39 respondents (81.2%) then from the results of spearman rho test with significance level a= 0.05 got the significance value p (value) 0.000 and correlation of 0.629 (Strong relationship level). The result of the analysis shows that there is a relationship between the duration of IUD family planning and the incidence of menorrhagia on IUD family planning acceptors in Sumolawang village, Puri sub-district, Mojokerto regency. This is triggered by the process of adaptation performed by the organ (womb) in the body. Along with the long use of IUD the body will begin to adapt to contraceptives that are installed.Keywords: Menorrhagia, duration used of IUD